Library Room Access System Using RFID Based Microcontroller Nodemcu ESP8266 - Agnes Marita Apriliani; Muhammad Rofiq (Procedia of Engineering and Life Science, 2021)
At this time, the library visitor access system uses manual filling of visitor lists, so it is not efficient. With this, the library room access system can use RFID so that visitors' data can be well structured. The design of this library room access system tool uses the Nodemcu esp8266 microcontroller. This tool works when the RFID tag provides input to the RFID reader and the existing data will be processed by the microcontroller to determine whether the ID data has been registered or not. If already registered, the data will immediately go to the visitor list according to the existing ID, whereas if not registered, it will enter the new member registration to fill in new member data, namely by filling in the number, name, gender and ID number. The result of the work of this tool is that the tool can work properly and RFID can read ID when the RFID tag and library room access systems can run properly. This tool is expected to make it easier for library visitors to fill in the visitor list without having to write it on a paper.